Modelling the impact of agriculture expansion on water scarcity in Xinjiang, China - Ying Guo; Yanfang Wang; Chao Zhao; Min Liu; Xiaolong Zhang; Yanjun Shen (Ecological Indicators, 2025)
Quantitative evaluation of changes in water supply and demand, water scarcity, and their influencing factors is essential for the sustainable management of regional water resources, food production, and ecological health. In this study, a distributed climate-water-ecology-economy (CWEE) comprehensive water demand model was established to estimate the spatial and temporal changes in socio-economic and ecological water demand. Annual and seasonal changes in water scarcity levels were spatially analyzed in Xinjiang. Subsequently, the logarithmic mean divisia index (LMDI) method was employed to decompose the contributions of three major impact factors to changes in water scarcity. The results indicated that the socio-economic water demand in Xinjiang increased significantly, with a 110% increase (1989–2017). The water scarcity index (WSI) showed an increasing trend in fluctuation, which was between 0.29 and 0.42 with a predominant moderate water scarcity before 2007 and higher than 0.5 with severe water scarcity after 2007. Monthly water scarcity was prominent in some basins. The improvement in water use efficiency helped to reduce socio-economic water demand. However, the sharp expansion of the planting scale and changes in the crop structure have led to a significant increase in socio-economic water demand (with agricultural water demand contributing over 93%), emerging as the primary factors exacerbating water scarcity. Therefore, controlling the crop planting scale, reasonably arranging the crop structure, and developing agricultural water-saving technologies are the main measures to relieve water scarcity and realize sustainable development in Xinjiang.